Influence of temperature on tire-pavement noise in hot climates: Qatar case - Okan Sirin (14603304) (2021)
The ambient air temperature greatly influences tire-pavement noise measurements. Therefore, various international standards recommended a temperature correction factor to compensate for noise measurements at varying temperatures. This temperature correction factor is developed based on the local environment (temperature varying from 5 °C to 35 °C) and generally varies with different pavements. Pavements in the Gulf region experienced harsh weather conditions, with temperatures often crossing 40 °C during summer. This study investigates the effect of air temperature on noise measurements in hot climatic conditions of Gulf regions. The On-Board Sound Intensity (OBSI) noise measurements technique was used to collect the noise data at different temperatures ranging from 25 °C to 43 °C. A linear regression analysis was performed to verify the relationship between noise and temperature. Three statistical criteria were selected to avoid parasitic phenomena and contamination of noise data during measurement. Statistical analysis demonstrated a strong relationship between noise intensity and temperature, especially at a frequency above 1250 Hz. Spectra analysis of the noise measurements also showed that the temperature coefficient is frequency-dependent, and generally, a frequency above 1250 Hz has a higher temperature coefficient. OBSI test results at various pavements with different mean texture depths of dense-graded pavement showed that the temperature coefficient varied from 0.052 dB/°C to 0.142 dB/°C. There is an apparent trend of decreasing temperature coefficient with increasing mean texture depth of dense graded asphalt pavements. However, no clear dependence on the temperature coefficient on the vehicle’s speed is observed in this study. Other Information Published in: Case Studies in Construction Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cscm.2021.e00651